The Soccer World Cup in Germany: A Major Sporting and Cultural Event - But Without Notable Business Cycle Effects - Karl Brenke; Gert G. Wagner (Weekly Report, 2006)
The upcoming World Cup has raised high expectations in Germany, not just for the national team, but for the economy as well. As the cyclical upswing has mainly been supported by exports so far, hopes have been growing recently that this sporting event will have a positive and stimulating effect on domestic demand - partly by increasing consumer confidence - and so enable the upswing to gain breadth.1 The analysis of the macroeconomic effects of the Soccer World Cup presented here shows that this could only happen if the event brought a clear change in consumer and investment behavior, together with a change in future expectations. However, that is not to be expected. Nevertheless, the World Cup is of high socio-political significance due its importance as a sporting and cultural event. It is (yet another) piece in the mosaic of Germany's transition from an industrial to a service society.
Keywords: 330